EIC504 : Lexicology / Academy of Language Studies - UiTM, Academy of Language Studies (Universiti Teknologi MARA (UiTM), 2023)
The course introduces students to lexicology by exploring the fundamental concepts in lexicology and how it is related to the other branches of linguistics. The course explains the historical development of English vocabulary, the conception of words, and the different word-formation process and meaning relations of words. The course also enables students to apply the lexicological knowledge through a small-scale corpus-based study involving concordancing software and analysis of texts from various social and professional contexts.